2017
DOI: 10.37285/ijpsn.2017.10.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Evaluation of Antinociceptive Effects of Bioactive Guided Fractions of Barleria prionitis

Abstract: Barleria prionitis Linn.(Acanthaceae) is a prickly shrub and traditionally whole plant is used as anti-inflammatory, expectorant, analgesic, diuretic, antirheumaticand antidiabetic. This study was conducted to investigate the antinociceptive and CNS depressant activity of ethanolic extract and the fractions of B. prionitis in mice. Ethanol extract and its fractions were tested at a dose of 200 and 400 mg/kg. Ethanol, petroleum ether and chloroform fractions demonstrated significant antinociceptive activity at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although analgesic drugs are available and efficient in reducing pain, their repetitive application can cause several side effects such as tolerance and physical dependence [ 244 , 245 ]. Regarding the genus Barleria , the literature reports only one study conducted by Begum et al [ 246 ], who investigated the effects of ethanol, chloroform, and petroleum ether extracts of the aerial parts of B. prionitis in Swiss albino mice at doses of 200 and 400 mg/kg. Overall, their study indicated that all the three extracts demonstrated significant analgesic effects in mice, with inhibition proportions of 30.36%, 59.40%, and 33.70% when tested at 400 mg/kg.…”
Section: Biological Activities Of Extracts Fractions and Isolated Compounds From Barleriamentioning
confidence: 99%
“…Although analgesic drugs are available and efficient in reducing pain, their repetitive application can cause several side effects such as tolerance and physical dependence [ 244 , 245 ]. Regarding the genus Barleria , the literature reports only one study conducted by Begum et al [ 246 ], who investigated the effects of ethanol, chloroform, and petroleum ether extracts of the aerial parts of B. prionitis in Swiss albino mice at doses of 200 and 400 mg/kg. Overall, their study indicated that all the three extracts demonstrated significant analgesic effects in mice, with inhibition proportions of 30.36%, 59.40%, and 33.70% when tested at 400 mg/kg.…”
Section: Biological Activities Of Extracts Fractions and Isolated Compounds From Barleriamentioning
confidence: 99%